Respuesta :

Answer: y=0 and x=3

Step 1: Solve for x in 2x+9y=6.

[tex]2x+9y=6[/tex]

[tex]2x=6-9y[/tex] (Subtract 9y from both sides)

[tex]x=3 - 4.5y[/tex]( Divide both sides by 2)

Step 2: Replace x with 3-4.5y

[tex]-7x - 8y = -21\\-7(3-4.5y) - 8y = -21\\[/tex]

Step 3: Solve for y

[tex](-21)+31.5y-8y=(-21)[/tex] (By looking at this, we can determine that y=0)

Step 4: Replace y with 0

[tex]2x+9y=6\\2x+9(0)=6\\2x=6\\[/tex]

[tex]x=3[/tex] (Divide both sides 2)

Therefore, y=0 and x=3

   

Answer: y=0 and x=3

Step-by-step explanation:

ACCESS MORE